Evaluation of Gingival Pigmentation and Related Factors on Former Smokers - Samir Goyushov; Cihan Ateş; Süleyman Emre Meşeli (eJournal of Oral Maxillofacial Research)
Objectives: Gingival pigmentation, the most common etiological factor of which is smoking, is a clinical condition that causes aesthetic complaints. Due to the dose-dependent effect of smoking, gingival pigmentation may present regression following cessation. This cross-sectional study aimed to evaluate gingival pigmentation in former tobacco consumers and compare with current ones.